The modus operandi and its uses in Arabic: A semantic morphological study - Al–Bannaa, Wisam Majeed Hasan (Al-Adab Journal, 2021)
Perhaps the interest in the linguistic structure and the changes that affect it and the connotations it contains was not without us from tracking and observing the ancients such as Hebron, Sibawayh, Al-Farabi, Ibn Faris and Ibn Jinni. Perhaps the system of polarization in the single structure, and its transformation from one form to another by the way of derivation, and the issue of attaching the building in the meaning is evidence of evidence for Their effort and what they tried to memorize from the genius of the language and followed them on this disagreement of the ancient and modernists analyze, explain, compare and deduce. Perhaps the formula (effective) is among the formulas that have not been devoted to research that collects the scattered issues in the stomachs of linguistic sources, which is what encouraged me to devote to this formula a study that collects its scattered kernels according to an approach that requires tracking the property of the building, i.e. what was said in its derivation, what this increase indicates and the meaning of exaggeration Its presence in nouns and adjectives and their use is a plural form and its connotations. And the appearance of this combination in the Holy Qur’an and the meaning of exaggeration in it, the difference between it and the actions of dilution, and the disagreement in some terms between this weight and the weight of two actions, leading to the conclusion and the sources, I ask God to grant success in knowledge and action.